Lactonase-mediated inhibition of quorum sensing largely alters phenotypes, proteome, and antimicrobial activities in Burkholderia thailandensis E264 - Gonzales, Mélanie; Plener, Laure; Armengaud, Jean; Armstrong, Nicholas; Chabrière, Éric; Daudé, David (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Burkholderia thailandensis is a study model for Burkholderia pseudomallei, a highly virulent pathogen, known to be the causative agent of melioidosis and a potential bioterrorism agent. These two bacteria use an (acyl-homoserine lactone) AHL-mediated quorum sensing (QS) system to regulate different behaviors including biofilm formation, secondary metabolite productions, and motility. Methods Using an enzyme-based quorum quenching (QQ) strategy, with the lactonase SsoPox having the best activity on B. thailandensis AHLs, we evaluated the importance of QS in B. thailandensis by combining proteomic and phenotypic analyses. Results We demonstrated that QS disruption largely affects overall bacterial behavior including motility, proteolytic activity, and antimicrobial molecule production. We further showed that QQ treatment drastically decreases B. thailandensis bactericidal activity against two bacteria (Chromobacterium violaceum and Staphylococcus aureus), while a spectacular increase in antifungal activity was observed against fungi and yeast (Aspergillus niger, Fusarium graminearum and Saccharomyces cerevisiae). Discussion This study provides evidence that QS is of prime interest when it comes to understanding the virulence of Burkholderia species and developing alternative treatments.